Evaluation of nitric oxide releasing polymers for wound healing applications - Wold, Kathryn A., author; Reynolds, Melissa, advisor; Henry, Charles, committee member; Kipper, Matt, committee member; Popat, Ketul, committee member; Williams, John, committee member (Colorado State University. Libraries, 2015)
Chronic, non-healing wounds afflict millions of Americans and represent a costly burden to the healthcare industry. In addition, the overuse and misuse of antibiotics has triggered the widespread emergence of drug-resistant bacteria, making the treatment of infected wounds more challenging. As a result, improved methods for wound care incorporating antibiotic-alternative bactericidal agents are in high demand. Recent wound care advances have focused on the development of dressings incorporating physical structures and biological components which mimic those encountered in a natural wound environment. Nitric oxide (NO), an endogenously produced molecule upregulated to promote cellular function and bactericidal activity during wound healing, has been harnessed in material systems and studied for wound healing potential. This work describes the characterization, bactericidal activity, cell functionality and processing of two NO-releasing polymer systems, one water-soluble and another water-insoluble. The results of this work demonstrate the capability of these polymeric NO-releasing materials to promote high log reductions of planktonic bacteria. Additionally, polymer dosages that promote cell survival and induce cytotoxicity in eukaryotic cells have been determined and nano-scale polymer fibers that maintain NO release properties have been processed. These results represent qualities beneficial towards the development of enhanced materials for the treatment of chronic infected wounds.
Keywords: biodegradable materials; nitric oxide; wound healing; electrospinning; antibacterial; polymers